1997
DOI: 10.1080/0267257x.1997.9964514
|View full text |Cite
|
Sign up to set email alerts
|

Effects of performance appraisal systems on marketing managers

Abstract: This study investigates the effects of features of performance appraisal systems (PAS) on marketing managers' behavioural and psychological responses. More specifically, four characteristics of performance appraisal systems (output PAS, behaviour PAS, document PAS and interpersonal PAS) and four key criterion variables (subordinate defensiveness, bureaucratic behaviour, invalid/misleading data reporting and satisfaction with the appraisal system) are considered. A survey of US marketing managers was conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…Volume 10, Number 4 Cappelli and Conyon (2018) stated that the evaluation of an employee's job performance is a standard practice in every organization; furthermore, they specified that performance appraisal directly influences employee work outcomes to different extents, such as employee bonuses, burnout, employee promotions, and turnover. Stathakopoulos (1997) stated that the purpose of his study was to explore the influence of the factors of performance appraisal system on managerial responses, so he found that the performance appraisal system has direct effects on dysfunctional behavior and satisfaction with the appraisal system.…”
mentioning
confidence: 99%
“…Volume 10, Number 4 Cappelli and Conyon (2018) stated that the evaluation of an employee's job performance is a standard practice in every organization; furthermore, they specified that performance appraisal directly influences employee work outcomes to different extents, such as employee bonuses, burnout, employee promotions, and turnover. Stathakopoulos (1997) stated that the purpose of his study was to explore the influence of the factors of performance appraisal system on managerial responses, so he found that the performance appraisal system has direct effects on dysfunctional behavior and satisfaction with the appraisal system.…”
mentioning
confidence: 99%